Study on the Performance Measure of Information Retrieval Models - Hua Jiang (2009 International Symposium on Intelligent Ubiquitous Computing and Education : 15-16 May 2009, 2009)
Different information retrieval models produce different retrieval results, and have different efficiencies. The paper firstly introduced the basic information retrieval process, and then listed three types of information retrieval models according to two dimensions and their relationships, and lastly gave out related calculation formulas for performance measure of information retrieval models.